2021
DOI: 10.1063/5.0033869
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of self-oscillating twin jets

Abstract: This study is focused on the behavior of self-oscillating twin jets emanating from round and square cross section nozzles into a narrow cavity. Computational fluid dynamics simulations are carried out in a confined rectangular cavity using the Reynolds stress turbulence model. Flow field characteristics are evaluated at nozzle spacing-to-diameter ratios (S/d) of 2, 3, 4, 5, at a jet Reynolds number of 27 000 based on nozzle exit velocity and diameter (d). Effects of nozzle spacing on the frequency of oscillati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…The domain length of the present flow field is comparable to previous studies. 9,15,17 An unstructured mesh with triangular elements has been used in the computational domain generated by using different mesh methods available in the grid generation tool AN-SYS workbench. When a turbulent free jet is issued into a quiescent ambient atmosphere, it experiences strong velocity gradients in the streamwise, transverse, and span wise directions.…”
Section: Numerical Methodology Computational Solvermentioning
confidence: 99%
See 1 more Smart Citation
“…The domain length of the present flow field is comparable to previous studies. 9,15,17 An unstructured mesh with triangular elements has been used in the computational domain generated by using different mesh methods available in the grid generation tool AN-SYS workbench. When a turbulent free jet is issued into a quiescent ambient atmosphere, it experiences strong velocity gradients in the streamwise, transverse, and span wise directions.…”
Section: Numerical Methodology Computational Solvermentioning
confidence: 99%
“…It was observed that the turbulent intensities of the combined jet increase progressively by increasing the S / D e ratio. Mosavati et al 15 investigated the round and square twin jets issuing into a narrow cavity using the Reynolds stress turbulence model at four different S / D e ratios and reported that the nozzle shape of the square and round twin jets does not significantly affect the jet decay. The effects of nozzle orientation on mixing and turbulent properties of elliptical twin jets were studied experimentally by Morris et al 16 It was found that the mean velocity does not vary significantly with orientation.…”
Section: Introductionmentioning
confidence: 99%
“…The main finding results was that the width of the twin jets spreads linearly downstream and grows with nozzles spacing and the merging length of the two jets can be increased either by reducing nozzles spacing or increasing Mach number. More recently, a numerical study focused on the characteristics of self-oscillating twin jets using the Reynolds Stress Turbulence Model [14]. Many nozzles spacing are used with a fixed Reynolds number (Re = 27000).…”
Section: Introductionmentioning
confidence: 99%